International comparisons of prices and output - Daly, D. J.; National Bureau of Economic Research (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1972)
This book concerns the use of national income concepts and data to appraise the supply and output of a national economies and some related aspect of international trade
"Seven papers presented at the sessions of the Conference on Research in Income and Wealth held in May 1970 at York University in Toronto."
Includes bibliographical references and index.
mf 21/01/2019
Loans
Keywords: National income; Prices